2021
DOI: 10.1094/pdis-11-20-2492-re
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Long-Term Bare Fallow During the Winter-Wheat Growth Season on the Soil Chemical Properties, Fungal Community Composition, and the Occurrence of Maize Fungal Diseases in North China

Abstract: On the North China Plain, one of the most water-deficient regions in China, bare fallow has been implemented over a large-scale area to conserve water during the growth season of water-intensive winter wheat since 2015. However, the effects of this bare fallow on fungal community and the occurrence of crop diseases are poorly understood. Here we measured soil chemical properties, fungal community composition and the occurrence of crop diseases after 15 years of long-term fallow (continuous maize or soybean) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 70 publications
1
5
0
Order By: Relevance
“…Significant correlations between these soil properties and the soil fungal community composition indicated that changes in the soil nutrients could be the major controlling factor of fungal community composition between the prior and new systems ( Figure 2A2 ). Moreover, the positive effects of the non-fertilized new rotation systems on the soil fungal diversity were in line with previous studies, which could be attributed to new niches provided by the nutrient-rich plant residue from the legumes ( Ding et al, 2017 ; Thapa et al, 2021 ; Wang Y. et al, 2021 ). These results indicated that soil fungal response to the new rotation systems was as rapid as the changes in the soil nutrients.…”
Section: Discussionsupporting
confidence: 90%
“…Significant correlations between these soil properties and the soil fungal community composition indicated that changes in the soil nutrients could be the major controlling factor of fungal community composition between the prior and new systems ( Figure 2A2 ). Moreover, the positive effects of the non-fertilized new rotation systems on the soil fungal diversity were in line with previous studies, which could be attributed to new niches provided by the nutrient-rich plant residue from the legumes ( Ding et al, 2017 ; Thapa et al, 2021 ; Wang Y. et al, 2021 ). These results indicated that soil fungal response to the new rotation systems was as rapid as the changes in the soil nutrients.…”
Section: Discussionsupporting
confidence: 90%
“…Soils in Jiamusi were significantly enriched in genes associated with carbohydrate metabolism, which were positively correlated with the high content of soil organic matter. Soil organic matter can provide nutrients and promote multiplication of microbes, ultimately, indirectly promoting the capacity of carbon metabolism [ 11 ]. With lower inputs of plant-derived organic carbon, desert communities have lower relative abundances of genes associated with nutrient cycling and the catabolism of plant-derived organic compounds compared with forests, grasslands, and tundra [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Soil microbes not only breakdown organic matter and minerals, they also secrete secondary metabolites that can regulate plant growth [ 7 9 ]. Microbes in soil can cause disease or help protect against disease [ 10 , 11 ]. Soil microbial communities and functions have strong spatial variability [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Soil microbes not only breakdown organic matter and minerals, they also secrete secondary metabolites that can regulate plant growth [7][8][9]. Microbes in soil can cause disease or help protect against disease [10,11]. Soil microbial communities and functions have strong spatial variability [12].…”
Section: Introductionmentioning
confidence: 99%